Germination pattern and quality resilience of West Bangka local rice seeds during storage in various media - Marini, Marini; Mustikarini, Eries Dyah; Kartika, Kartika (Universitas Trunojoyo Madura, 2025)
Local rice seeds from Bangka have great potential for food security. Seeds stored in the wrong place can experience a decrease in quality. This study aims to assess the germination pattern and quality resilience of local Bangka rice seeds under different storage methods. The research was conducted from February to September 2024 at the Seed Laboratory and Plant Breeding, Bangka Belitung University. The study used a completely randomized design (CRD) with a split plot pattern. The first factor consists of six accessions of local rice from Bangka (Mukot, Jawa, Ungu, Pulut Hitam, Balok Merah, and Mayang Hutan). The second factor comprises seven storage methods (cans, 40-micron plastic, 120-micron plastic, plastic bags, plastic containers, nursery trays, and panicles). This study shows significant differences in the germination patterns of local Bangka rice seeds stored in various media for 0, 2, 4, and 6 months. The Jawa access had the highest germination rate (78.8%) with an optimal storage time of 4 months, while storing seeds using panicles gave the best results (82.3%) compared to other media. The Balok Merah access excelled in maintaining seed quality. The local Bangka rice access, namely Jawa and Balok Merah, stored using the panicle storage method, can be applied by farmers and the community to maintain seed quality.